Dynamic reciprocal relations of achievement goals with daily experiences of academic success and failure: An ambulatory assessment study. (October 2022) - Neubauer, Andreas B.; Schmidt, Andrea; Schmiedek, Florian; Dirk, Judith
Abstract: Achievement goals have been linked to achievement in various educational settings. The present work explored day-to-day variations in achievement goals (mastery, performance-approach, performance-avoidance) and their associations with daily experiences of academic success and failure. Ambulatory assessment data from 108 students in Grade 5 were collected, with daily assessments of achievement goals in the morning and end-of-day reports of academic success and failure. Dynamic structural equation models revealed reciprocal within-person effects between mastery goals and academic success. Academic success was further associated with higher mastery and performance-approach goals in the next morning. Academic failure was linked to both performance goals, though this association was not robust in all sensitivity analyses. Higher average daily academic success and lower average academic failure were linked to better academic achievement one year later. Findings suggest meaningful within-person dynamics among goals and daily academic success and failure. Highlights: Children's achievement goals show state-like variation from day to day. Daily mastery goals are linked to more academic success. Daily performance-avoidance goals are associated with academic failure. After more successful days, children set more achievement goals in general.